Αυτόματη διαχείριση δικτυακών τοπολογιών και υπηρεσιών - Μαντάος, Γρηγόρης-Παναγιώτης (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Ηλεκτρολόγων Μηχανικών και Μηχανικών Υπολογιστών. Τομέας Επικοινωνιών, Ηλεκτρονικής και Συστημάτων Πληροφορικής, 2018)
The use of virtual machines for simulation, as well as regular configuration and use of networking components such as routers and bridges, has significantly affected the role of systems engineers and administrators over the last few years. Virtual routers are essentially software running on virtual machines and support all of the routing protocols and functions of a physical router. The flexibility that these virtualization technologies provide allows for the fast and seamless development of such software on physical hosts, giving researchers and students alike the means to experiment with network topologies without being limited by the resources of physical machines. Combining this lift of physical limitations with the tools and methodologies of software development, we now have the ability to treat such networking components with a layer of abstraction, creating, configuring and deleting them at will. The purpose of this project is to develop an administrative graphical user interface that will allow the design of network topologies of variable size and complexity as well the automated deployment of said topologies on the available hardware.